Uji Toleransi Logam Berat Bakteri Hidrokarbonoklastik dan Uji Kemampuan Micrococcus sp. LII61 dalam Menurunkan Kromium (Cr VI), Tembaga (Cu II), Seng (Zn II) - Abidin, Achmad Zainal; Renjana, Elga; Fatimah, Fatimah; Ni’matuzahroh, Ni’matuzahroh (Bioedukasi: Jurnal Pendidikan Biologi, 2019)
This research aimed to know: (1) tolerance level of hydrocarbon-degrading bacteria collected from Biology Laboratory of Airlangga University i.e. Acinetobacter sp P2(1) Bacillus subtilis 3KP, Micrococcus sp. LII61, Pseudomonas putida T1(8), at various concentration of heavy metal chromium (Cr6+), copper (Cu2+), zinc (Zn2+), and combination of that three metals; (2) growing ability of selected bacteria in lowering metals concentration; and (3) reduction percentage of metal concentration by selected bacteria. Tolerance test was performed using streak plate method on two types of solid mediums, i.e. Mineral Salt Medium (MSM) agar and Mueller-Hinton Agar (MHA) with a stratified concentration and 72 hours of incubation time. Bacterial growth and metal concentration reduction test were carried out in liquid medium containing single metal or combined metals. Viability of bacteria was calculated using Total Plate Count (TPC) method. Logarithmic of TPC were analyzed statistically using Brown-Forsythe test followed by Games-Howell. The results showed: (1) All bacteria was resistant to either single heavy metal or combined metals on both medium. However, Micrococcus sp. LII61, had the highest tolerance compared to the other three bacteria, which was able to grow at Zn+2 1000 ppm in both medium. Micrococcus sp. LII61, was the selected bacteria to be tested for its ability to reduce heavy metal by single heavy metal and combined metals for 3 and 7 days of incubation time. (2) Ability levels of Micrococcus sp. LII61, to grow in some heavy metals was Zn2+ > Cu2+ > Cr6+ consecutively. (3) Ability levels of Micrococcus sp. LII61, in reducing heavy metals was Cu2+ > Zn2+ > Cr6+ consecutively. Percentage decrease of Cu2+ in single metal was 66.15%, while in combination metals was 54.25% at 3 days incubation. Percentage decrease of Cu2+ after seven day incubation in single metals and combination metals were 90.13% and 74.72% respectively.